Chronic Pelvic Pain Development and Prostate Inflammation in Strains of Mice With Different Susceptibility to Experimental Autoimmune Prostatitis - Breser, Maria Laura (2016)
BACKGROUND: Experimental autoimmune prostatitis (EAP) is an autoimmune inflammatory disease of the prostate characterized by peripheral prostate-specific autoimmune responses associated with prostate inflammation. EAP is induced in rodents upon immunization with prostate antigens (PAg) plus adjuvants and shares important clinical and immunological features with the human disease chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). METHODS: EAP was induced in young NOD, C57BL/6, and BALB/c male mice by immunization with PAg plus complete Freund́s adjuvant. Tactile allodynia was assessed using Von Frey fibers as a measure of pelvic pain at baseline and at different time points after immunization. Using conventional histology, immunohistochemistry, FACS analysis, and protein arrays, an interstrain comparative study of prostate cell infiltration and inflammation was performed. RESULTS: Chronic pelvic pain development was similar between immunized NOD and C57BL/6 mice, although the severity of leukocyte infiltration was greater in the first case. Coversely, minimal prostate cell infiltration was observed in immunized BALB/c mice, who showed no pelvic pain development. Increased numbers of mast cells, mostly degranulated, were detected in prostate samples from NOD and C57BL/6 mice, while lower total counts and resting were observed in BALB/c mice. Prostate tissue from NOD mice revealed markedly increased expression levels of inflammatory cytokines, chemokines, adhesion molecules, vascular endothelial growth factor, and metalloproteinases. Similar results, but to a lesser extent, were observed when analyzing prostate tissue from C57BL/6 mice. On the contrary, the expression of the above mediators was very low in prostate tissue from immunized BALB/c mice, showing significantly slight increments only for CXCL1 and IL4. CONCLUSIONS: Our results provide new evidence indicating that NOD, C57BL/6, and BALB/c mice develop different degrees of chronic pelvic pain, type, and amount of prostate cell infiltration and secretion of inflammatory mediators. Our results corroborate and support the notion that mice with different genetic background have different susceptibility to EAP induction.